Bauhinia pottsii G. Don var pottsii DARI KALIMANTAN DITEMUKAN KEMBALI - Astuti, Inggit Puji; Magandhi, Mahat; Suratman, Maman; Maulida, Risa (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2012)
Bauhinia is one of the largest genus in Caesalpiniaceae family and distributed in all tropical area. One among 300 species of Bauhinia is Bauhinia pottsii G. Don. This species is distributed from Southern Myanmar, Thailand, Cambodia, Malay Peninsular, Borneo, Sumatra, Jawa, Bali and Lesser Sunda islands. It was recorded that one specimen was originated from East Kalimantan and collected in 1925. During exploration in Kampung Temula, Kecamatan Nyuatan, Kabupaten Kutai Barat, East Kalimantan, Bauhinia pottsii G. Don var pottsii was found after about 87 years. Bauhinia is one of the largest genus in Caesalpiniaceae family and distributed in all tropical area. One among 300 species of Bauhinia is Bauhinia pottsii G. Don. This species is distributed from Southern Myanmar, Thailand, Cambodia, Malay Peninsular, Borneo, Sumatra, Jawa, Bali and Lesser Sunda islands. It was recorded that one specimen was originated from East Kalimantan and collected in 1925. During exploration in Kampung Temula, Kecamatan Nyuatan, Kabupaten Kutai Barat, East Kalimantan, Bauhinia pottsii G. Don var pottsii was found after about 87 years.